Catalytic hydrogenolysis of alkali lignin in supercritical ethanol over copper monometallic catalyst supported on a chromium-based metal–organic framework for the efficient production of aromatic monomers - Tran, My Ha; Phan, Dieu Phuong; Nguyen, Thuy Ha; Kim, Han Bom; Kim, Jinsoo; Park, Eun Duck; Lee, Eun Yeol (Bioresource Technology, 2021)
The catalytic hydrogenolysis of lignin has been reported as an effective approach for lignin depolymerization owing to its high efficiency for aromatic monomer production. In this study, a series of copper monometallic catalysts over an MIL-101(Cr) support were synthesized and used for the catalytic hydrogenolysis of alkali lignin using supercritical ethanol. First, the optimal copper catalyst for lignin hydrogenolysis was selected. Subsequently, the reaction conditions for catalytic hydrogenolysis were systematically optimized to maximize the total monomer yield. The optimal conditions were determined to be 6 h of reaction time, 20 min of sonication pretreatment, 50% catalyst loading, and 5% lignin loading. Under these conditions, an aromatic monomer yield of 38.5% was obtained; this depolymerized lignin stream, which is mainly composed of G-type monomers, can serve as a promising aromatic feedstock and carbon source for further microbial upgrading and bioconversion to produce various value-added products.
Keywords: Alkali lignin; Aromatic monomers; Catalytic hydrogenolysis; Chromium-based; Copper catalyst; Effective approaches; Lignin depolymerization; Metalorganic frameworks (MOFs); Monometallic catalysts; Supercritical ethanol; Alkalies; Catalysis; Chromium; Copper; Ethanol; Lignin; Metal-Organic Frameworks; Alkali lignin; Aromatic monomers; Catalytic hydrogenolysis; Copper catalyst; Supercritical ethanol